Preparation of laser direct writing photoresist containing heteropoly acid with adjustable refractive index and patterning method based on the photoresist
Patent Information
- Application Number
- CN202310699369.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-06-13
AI Technical Summary
[0036] This solid-state photoresist abandons traditional methods and boasts a simple manufacturing process. It eliminates the use of metal oxide nanoparticles as fillers, employing an innovative method to uniformly disperse heteropolyacids within the photoresist without the need for additional dispersants to promote dispersion. It also eliminates the need to introduce sulfur or halogen atoms into monomers or polymers. The refractive index of this solid-state photoresist is adjustable within the range of 1.4-1.8; the film thickness is adjustable within the range of 200nm-10μm; the transmittance of the film within the target area is greater than 90%; the filler is uniformly dispersed with small particle size and low surface roughness; and two-photon lithography can be used to fabricate 2D and 3D structures of various shapes.
Smart Images

Figure CN116719207B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical fields of hybrid photoresists, femtosecond laser direct writing, and optical materials, and specifically relates to a method for preparing a laser direct writing photoresist with adjustable refractive index and a patterning method based on the photoresist.
[0002] Background Introduction
[0003] The refractive index (n) of a material is one of the most important factors determining its suitability for optical applications, which typically require high n values and high transparency. This is most evident in the industrial production of solar cells, LEDs, OLEDs, optical lenses and filters, antireflective coatings, optical adhesives, and optical waveguides.
[0004] To meet the urgent and growing needs in these fields, two methods have been developed to tune the refractive index of photoresists. The first method involves synthesizing special monomers containing heavy atoms such as sulfur and halogens; the second involves mixing nanoparticles with different refractive indices into the photoresist. In the former case, the photoresist offers advantages in terms of weight and processability, but inherent limitations in chemical design make it difficult to achieve a refractive index greater than 1.8. On the other hand, nanoparticle hybrid materials have high potential for refractive index tuning; however, nanoparticles suffer from severe dispersion problems during hybridization because most nanoparticles tend to self-aggregate in solvents or polymer matrices due to strong particle attraction. Such aggregation does not tune the refractive index but increases opacity. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing a laser direct-write photoresist containing heteropolyacid with adjustable refractive index and a patterning method based on the photoresist.
[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a method for preparing a laser direct-write photoresist containing heteropolyacids, comprising the following steps:
[0008] S1: In a clean brown bottle, add the heteropoly acid to organic solvent A, shake slowly first, and then let it stand until it is completely transparent and uniform to obtain a heteropoly acid solution.
[0009] S2: In a clean brown bottle, add the film-forming resin to organic solvent B and sonicate until it is uniformly dispersed to obtain a film-forming resin solution.
[0010] S3: In a clean brown bottle, add the active monomer to organic solvent C, sonicate until uniformly dispersed, then add the photoinitiator to the solution, sonicate until uniformly dispersed, and obtain the active monomer solution.
[0011] S4: Take an appropriate amount of active monomer solution and heteropoly acid solution, mix them, and sonicate until the complex is evenly dispersed. Then, slowly add the film-forming resin solution dropwise to the mixed solution, shake slowly first, and then let it stand until the solution layering phenomenon disappears to obtain a laser direct-write photoresist containing heteropoly acid. Among them, based on the total mass of film-forming resin, active monomer, heteropoly acid and photoinitiator as 100%, the mass percentage contents of film-forming resin, active monomer, heteropoly acid and photoinitiator are 5-30wt%, 10-60wt%, 10-40wt%, and 0.25-5wt%, respectively.
[0012] The film-forming resin contains at least one of ester, carbonyl, and hydroxyl groups; the active monomer is a centrally branched acrylate monomer containing hydroxyl groups; and the heteropolyacid is selected from at least one compound conforming to the following general formula:
[0013] H m XY 12 O 40 ·nH2O
[0014] Where m = 3, 4 or 5, X is the central coordinating atom, Y is the polyacid atom, and n is the number of bound water molecules (n≥0, different heteropolyacids have different amounts of water of crystallization, this value is determined according to the heteropolyacid), where X is P, As, Si, Ge, Sn, Ti, Zr, B, Ce, Th or U, and Y is Mo, W or V.
[0015] Preferably, organic solvent A, organic solvent B, and organic solvent C are all selected from polar organic solvents containing a large number of carbonyl groups, ester groups, or hydroxyl groups, and each is independently selected from ethyl acetate, ethyl formate, dimethyl sulfoxide, and propylene glycol methyl ether acetate. More preferably, organic solvent A, organic solvent B, and organic solvent C are the same solvent.
[0016] Preferably, the film-forming resin is selected from at least one of polymethyl methacrylate, polyhydroxyethyl methacrylate, polyvinyl acetate, and polyvinyl alcohol. More preferably, the molecular weight of the film-forming resin is not higher than 20,000, with a molecular weight of 3,000-16,000 being the most desirable.
[0017] Preferably, the active monomer is selected from at least one of pentaerythritol triacrylate, pentaerythritol dimethacrylate, and pentaerythritol diacrylate.
[0018] Preferably, the photoinitiator is an oil-soluble photoinitiator that does not produce significant absorption at the target wavelength at the concentration used, and is selected from at least one of 7-diethylamino-3-thiophenecarboxycoumarin (DETC), photoinitiator 369 (Irgacure 369), photoinitiator 651 (Irgacure 651), and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (TPO).
[0019] Preferably, in step S1, the concentration of the heteropolyacid solution is 5%-50wt%, with 20-40wt% being the most desirable.
[0020] Preferably, in step S2, the concentration of the film-forming resin solution is 5-30 wt%, with 9-25 wt% being more desirable.
[0021] Preferably, in step S3, the concentration of the active monomer in the active monomer solution is 10-50 wt%, preferably 30-45 wt%; and the concentration of the photoinitiator is 0.25%-5% wt%, preferably 0.4%-2%.
[0022] Secondly, the present invention provides a patterning method based on the laser direct-write photoresist containing heteropolyacids, comprising the following steps:
[0023] R1: Spin coating: Make the laser direct-write photoresist containing heteropolyacids transparent and uniform; place the substrate on the spin coater, drop an appropriate amount of photoresist onto the substrate, and use a suitable rotation speed to spin coat the photoresist into a uniform film.
[0024] R2: Pre-baking: Place the spin-coated substrate on a baking device and heat it to completely remove the solvent;
[0025] R3: Laser direct writing device setup: Arrange the femtosecond laser, optical switch, alignment device, galvanometer, objective lens, and pressure platform sequentially along the optical path to form a laser direct writing device. Place the pre-baked substrate on the displacement stage of the laser direct writing device, and fill the gap between the substrate and the lens with refractive index oil.
[0026] R4: Turn on the laser direct writing device, focus the objective lens on the interface between the substrate and the photoresist; load the pre-designed structure, set the laser power and scanning speed, and start the direct writing experiment;
[0027] R5: Develop the direct-written substrate to obtain the photoresist pattern.
[0028] Preferably, in step S1, the carrier is pre-cleaned and selected from one of glass, quartz, silicon, and silicon nitride, with a thickness preferably 0.15-0.3 mm.
[0029] Preferably, in step R1, the spin coating speed is 500-3000 rpm and the spin coating time is 30-60 s.
[0030] Preferably, in step R2, the pre-baking temperature is 90-95℃ and the heating time is 1-5 min.
[0031] In step S4 of this invention, the femtosecond laser wavelength is 400-900 nm, with the optimal wavelength being one of 780 nm, 640 nm, 525 nm, 517 nm, or 405 nm. The femtosecond laser focus enables the photoinitiator to undergo nonlinear absorption, thereby causing the initiator to decompose into free radicals and further initiate the free radical polymerization of monomers. By controlling the femtosecond laser power and the movement of the piezoelectric platform through software, the focus can be controlled to scan layer by layer within the photoresist to obtain a pre-designed 2D or 3D pattern. Preferably, in step R4, the laser power is 1-50 mW, and the scanning speed is 1000-10000 μm / s.
[0032] After step S4, the monomers scanned by the laser focus inside the photoresist undergo free radical polymerization, transforming from free monomers to a cross-linked state. The cross-linked polymer and the monomers have different solubilities in the developing solution; the unreacted monomers have higher solubility. Therefore, step S5 utilizes this solubility difference to remove the unreacted photoresist. Preferably, in step R5, the developing process is as follows: first developing in a primary developing agent for 5-30 seconds, then developing in a secondary developing agent for 5-30 seconds; the primary developing agent is selected from one or a mixture of several of acetone, ethanol, isopropanol, propylene glycol methyl ether acetate, toluene, xylene, and dichloromethane; the secondary developing agent is selected from isopropanol or ethanol.
[0033] The principle of this invention is:
[0034] Compared to traditional photoresist solutions that use metal oxide nanoparticles as fillers for hybridization, the laser direct-write photoresist containing heteropolyacids provided in this invention uses heteropolyacids with different refractive indices as fillers. The refractive index of the photoresist can be easily controlled by changing the type and content of heteropolyacids. The heteropolyacids themselves are about 1 nanometer in size, which is much smaller than metal oxide nanoparticles. Even if they aggregate, they will not form very large particles. Although heteropolyacids are basically insoluble in organic solvents, film-forming resins with ester groups, carbonyl groups, and / or hydroxyl groups can act as both film-forming resins and dispersants. These chemical bonds can coordinate with heteropolyacids to counteract the attraction between heteropolyacids. The centrally branched acrylate monomers containing hydroxyl groups can act as complexes and active monomers of heteropolyacids. With the introduction of photoinitiators, different 2D and 3D structures can be obtained using two-photon lithography.
[0035] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0036] This solid-state photoresist abandons traditional methods and boasts a simple manufacturing process. It eliminates the use of metal oxide nanoparticles as fillers, employing an innovative method to uniformly disperse heteropolyacids within the photoresist without the need for additional dispersants to promote dispersion. It also eliminates the need to introduce sulfur or halogen atoms into monomers or polymers. The refractive index of this solid-state photoresist is adjustable within the range of 1.4-1.8; the film thickness is adjustable within the range of 200nm-10μm; the transmittance of the film within the target area is greater than 90%; the filler is uniformly dispersed with small particle size and low surface roughness; and two-photon lithography can be used to fabricate 2D and 3D structures of various shapes. Attached Figure Description
[0037] Figure 1 This is a threshold array diagram obtained by laser direct writing of the heteropolyacid solid photoresist of Example 1.
[0038] Figure 2 It is based on Figure 1 The obtained photoresist threshold curve.
[0039] Figure 3 This is the transmittance curve of the photoresist film after curing in Example 3 at 400-1700nm.
[0040] Figure 4 It is a 3D optical device obtained by laser direct writing using the heteropolyacid solid photoresist in Example 2.
[0041] Figure 5 The microlens is obtained by laser direct writing of the heteropolyacid solid photoresist in Example 3.
[0042] Figure 6 The photonic leads are obtained by laser direct writing of the heteropolyacid solid photoresist in Example 4. Detailed Implementation
[0043] The present invention will be further illustrated below with reference to examples, but these examples are not intended to limit the present invention.
[0044] Example 1
[0045] 1) Gel preparation: Take 0.375g of tungstic acid dodecahydrate into a clean brown reagent bottle, add 1mL of ethyl acetate, tighten the cap, and invert the bottle several times to mix evenly. Then let it stand until uniformly dispersed. Take 0.2g of polymethyl methacrylate (molecular weight 6000) into a clean brown reagent bottle, add 1mL of ethyl acetate, tighten the cap, and continue sonicating until uniformly dispersed. Take 0.35g of pentaerythritol triacrylate (PETA) into a clean brown reagent bottle, add 0.65mL of ethyl acetate, tighten the cap, and continue sonicating until uniformly dispersed. Add 6mg of DTEC to the PETA solution and continue sonicating until uniformly dispersed. Add 400µL of tungstic acid solution to 300µL of PETA solution, gently shake, and continue sonicating until the complex is uniformly dispersed in the solution. Slowly add 300µL of polymethyl methacrylate solution dropwise to the mixture from the previous step, tighten the cap, invert the bottle several times to mix evenly, and then let it stand until uniformly dispersed.
[0046] 2) Spin coating and pre-baking: Before spin coating, allow the photoresist to stand for a period of time to ensure it is uniform and does not separate. Take an appropriate amount of photoresist and drop it onto a clean glass slide. Place the glass slide on a spin coater and spin coat the entire glass slide using parameters of 1000 rpm for 30 seconds and 3000 rpm for 60 seconds. Place the spin-coated glass slide on a hot plate and heat it at 90°C for 1 minute to remove all solvents.
[0047] 3) Laser Direct Writing: The dual-beam femtosecond laser direct writing system used in this invention includes a femtosecond laser source, a continuous laser source, a beam coupling system, a writing alignment device, a galvanometer, a piezoelectric platform, and an objective lens. The spin-coated glass slide obtained in step 2) is placed on the sample holder of the direct writing system. The gap between the objective lens and the glass slide is filled with refractive index oil (refractive index 1.518). The laser direct writing system is started, and the femtosecond laser focus is placed at the interface between the photoresist film and the glass slide. The femtosecond laser wavelength is 780nm, the femtosecond laser power adjustment range is 1-50mW, and the writing speed is 1000-10000μm / s. After loading the pre-set program, the threshold array direct writing experiment begins.
[0048] 4) Development: Immerse the written glass slide obtained in step 3) horizontally in propylene glycol methyl ether acetate for 15 seconds; after immersion, rinse with isopropanol for 15 seconds, and then lay it flat to air dry.
[0049] Figure 1 The image shows a threshold array obtained by direct laser writing of the heteropolyacid solid photoresist of Example 1. The array shows that the maximum writing speed of the heteropolyacid solid photoresist can reach 10 mm / s, and due to the memory effect in 3D writing, the speed achievable is even faster. Therefore, this photoresist has good photosensitivity and can be directly written with relatively low laser power at different scanning speeds.
[0050] Figure 2 It is based on Figure 1 The obtained photoresist threshold curve shows that a femtosecond laser power of 36.5mW is required for a writing speed of 10mm / s.
[0051] Example 2
[0052] 1) Gel preparation: Take 0.5g of tungstic phosphate dodecahydrate into a clean brown reagent bottle, add 1mL of propylene glycol methyl ether acetate, tighten the cap, and invert the reagent bottle several times to mix evenly, then let it stand until uniformly dispersed; Take 0.1g of poly(hydroxyethyl methacrylate) (molecular weight 9000) into a clean brown reagent bottle, add 1mL of propylene glycol methyl ether acetate, tighten the cap, and continue sonicating until uniformly dispersed; Take 0.4g of pentaerythritol diacrylate into a clean brown reagent bottle, add 0.6mL of propylene glycol methyl ether acetate, tighten the cap, and continue sonicating until uniformly dispersed; Add 8mg of IR 369 to the PEDA solution and continue sonicating until uniformly dispersed. Add 400 μL of tungstic acid solution to 300 μL of PEDA solution, gently shake and then sonicate until the complex is evenly dispersed in the solution; slowly add 300 μL of poly(hydroxyethyl methacrylate) solution to the mixture from the previous step, tighten the cap and invert the reagent bottle several times to mix evenly, then let it stand until evenly dispersed.
[0053] 2) Spin coating and pre-baking: Before spin coating, let the photoresist stand for a period of time to ensure it is uniform and does not separate. Take an appropriate amount of photoresist and drop it onto a clean glass slide. Place the glass slide on a spin coater and spin coat the entire glass slide at parameters of 500 rpm for 30 seconds and 1500 rpm for 60 seconds. Place the spin-coated glass slide on a hot plate and heat it at 95°C for 1 minute to remove all solvents.
[0054] 3) Laser Direct Writing: The dual-beam femtosecond laser direct writing system used in this invention includes a femtosecond laser source, a continuous laser source, a beam coupling system, a writing alignment device, a galvanometer, a piezoelectric platform, and an objective lens. The spin-coated glass slide obtained in step 2) is placed on the sample holder of the direct writing system. The gap between the objective lens and the glass slide is filled with refractive index oil (refractive index 1.518). The laser direct writing system is started, and the femtosecond laser focus is placed at the interface between the photoresist film and the glass slide. The femtosecond laser wavelength is 780nm, the femtosecond laser power is 50mW, and the writing speed is 50mm / s. After loading the pre-set program, the direct writing experiment of the 3D optical switch begins. The resulting optical switch is shown below. Figure 3 As shown.
[0055] 4) Development: Immerse the written glass slide obtained in step 3) horizontally in propylene glycol methyl ether acetate for 15 seconds; after immersion, rinse with isopropanol for 15 seconds, and then lay it flat to air dry.
[0056] Figure 4 The 3D optical switch obtained by laser direct writing of the heteropolyacid solid photoresist in Example 2 proves that 3D structure writing similar to liquid photoresist can be achieved by adjusting the component content and spin coating parameters to change the photoresist film thickness.
[0057] Example 3
[0058] 1) Gel preparation: Take 0.3g of molybdenum phosphate hydrate (Maclean, CAS51429-74-4) into a clean brown reagent bottle, add 1mL of DMSO, tighten the cap, and invert the bottle several times to mix evenly, then let it stand until uniformly dispersed; Take 0.15g of polyvinyl acetate (molecular weight 8000) into a clean brown reagent bottle, add 1mL of DMSO, tighten the cap, and continue sonicating until uniformly dispersed; Take 0.45g of pentaerythritol dimethacrylate into a clean brown reagent bottle, add 0.55mL of DMSO, tighten the cap, and continue sonicating until uniformly dispersed; Add 4mg of TPO to the pentaerythritol dimethacrylate solution and continue sonicating until uniformly dispersed. Add 400 μL of molybdenum phosphate solution to 300 μL of pentaerythritol dimethacrylate solution, gently shake and then sonicate until the complex is evenly dispersed in the solution; slowly add 300 μL of polyvinyl acetate solution to the mixture from the previous step, tighten the cap and invert the reagent bottle several times to mix evenly, then let it stand until evenly dispersed.
[0059] 2) Spin coating and pre-baking: Before spin coating, let the photoresist stand for a period of time to ensure it is uniform and does not separate. Take an appropriate amount of photoresist and drop it onto a clean glass slide. Place the glass slide on a spin coater and spin coat the entire glass slide at parameters of 1000 rpm for 30 seconds and 2000 rpm for 60 seconds. Place the spin-coated glass slide on a hot plate and heat it at 92°C for 1 minute to remove all solvents.
[0060] 3) Laser Direct Writing: The dual-beam femtosecond laser direct writing system used in this invention includes a femtosecond laser source, a continuous laser source, a beam coupling system, a writing alignment device, a galvanometer, a piezoelectric platform, and an objective lens. The spin-coated glass slide obtained in step 2) is placed on the sample holder of the direct writing system. The gap between the objective lens and the glass slide is filled with refractive index oil (refractive index 1.518). The laser direct writing system is started, and the femtosecond laser focus is placed at the interface between the photoresist film and the glass slide. The femtosecond laser wavelength is 780 nm, the femtosecond laser power adjustment range is 25 mW, and the writing speed is 5000 μm / s. After loading the pre-set program, the direct writing experiment begins.
[0061] 4) Development: Immerse the written glass slide obtained in step 3) horizontally in propylene glycol methyl ether acetate for 15 seconds; after immersion, rinse with isopropanol for 15 seconds, and then lay it flat to air dry.
[0062] Figure 3 This is the transmittance curve of the photoresist film after curing in Example 3, ranging from 400 to 1700 nm. It can be seen that the cured photoresist maintains a transmittance of over 90% in the wavelength range greater than visible light. Figure 5 The microlens is obtained by laser direct writing of the heteropolyacid solid photoresist in Example 3.
[0063] Example 4
[0064] 1) Gel preparation: Take 0.3g of molybdenum silicate dodecahydrate into a clean brown reagent bottle, add 1mL of ethyl formate, tighten the cap, and invert the reagent bottle several times to mix evenly, then let it stand until uniformly dispersed; Take 0.3g of polyvinyl alcohol (molecular weight 12000) into a clean brown reagent bottle, add 1mL of ethyl formate, tighten the cap, and continue sonicating until uniformly dispersed; Take 0.5g of pentaerythritol triacrylate into a clean brown reagent bottle, add 0.5mL of ethyl formate, tighten the cap, and continue sonicating until uniformly dispersed; Add 6mg of IR 651 to the pentaerythritol triacrylate solution, and continue sonicating until uniformly dispersed. Add 400 μL of molybdenum silicate solution to 300 μL of pentaerythritol triacrylate solution, gently shake and then sonicate until the complex is evenly dispersed in the solution; slowly add 300 μL of polyvinyl alcohol solution to the mixture from the previous step, tighten the cap and invert the reagent bottle several times to mix evenly, then let it stand until evenly dispersed.
[0065] 2) Spin coating and pre-baking: Before spin coating, let the photoresist stand for a period of time to ensure it is uniform and does not separate. Take an appropriate amount of photoresist and drop it onto a clean glass slide. Place the glass slide on a spin coater and spin coat the entire glass slide at parameters of 100 rpm for 30 seconds and 300 rpm for 60 seconds. Place the spin-coated glass slide on a hot plate and heat it at 95°C for 1 minute to remove all solvents.
[0066] 3) Laser Direct Writing: The dual-beam femtosecond laser direct writing system used in this invention includes a femtosecond laser source, a continuous laser source, a beam coupling system, a writing alignment device, a galvanometer, a piezoelectric platform, and an objective lens. The spin-coated glass slide obtained in step 2) is placed on the sample holder of the direct writing system. The gap between the objective lens and the glass slide is filled with refractive index oil (refractive index 1.518). The laser direct writing system is started, and the femtosecond laser focus is placed at the interface between the photoresist film and the glass slide. The femtosecond laser wavelength is 780nm, the femtosecond laser power adjustment range is 50mW, and the writing speed is 50mm / s. After loading the pre-set program, the direct writing experiment of the photonic leads begins.
[0067] 4) Development: Immerse the written glass slide obtained in step 3) horizontally in propylene glycol methyl ether acetate for 15 seconds; after immersion, rinse with isopropanol for 15 seconds, and then lay it flat to air dry.
[0068] Figure 6 The photonic leads obtained by laser direct writing of the heteropolyacid solid photoresist in Example 4 demonstrate the application potential of photoresist in the field of optical waveguides.
[0069] Table 1
[0070]
[0071] Note: Refractive index (before direct writing), film thickness, transmittance (1550nm) and surface roughness (Ra) were measured using the sample obtained in step 2) of each embodiment. Refractive index (after direct writing) was measured using the sample obtained after development of each embodiment. The refractive index was measured using a refractometer, the surface roughness (Ra) was measured using an AFM, and the transmittance was measured using a UV spectrophotometer.
[0072] Table 1 shows the refractive index and film thickness data of the photoresist before and after baking in the four examples. It can be seen that the refractive index of the heteropolyacid solid photoresist proposed in this invention can be adjusted within the range of 1.4-1.8. After curing, the refractive index of the photoresist increases slightly, indicating that the structure cured by femtosecond laser writing can still maintain the set refractive index range. The film thickness of the solid photoresist can be changed with different spin-coating parameters. Under high spin-coating conditions, the film thickness is in the nanometer range, reaching 285 nm in Example 1. Under low spin-coating conditions, the film thickness is in the micrometer range, reaching 4.7 μm in Example 4.
[0073] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a laser direct-write photoresist containing heteropolyacids, characterized in that: The preparation method includes the following steps: S1: In a clean brown bottle, add the heteropoly acid to organic solvent A, shake slowly first, and then let it stand until it is completely transparent and uniform to obtain a heteropoly acid solution. S2: In a clean brown bottle, add the film-forming resin to organic solvent B and sonicate until it is uniformly dispersed to obtain a film-forming resin solution. S3: In a clean brown bottle, add the active monomer to organic solvent C, sonicate until uniformly dispersed, then add the photoinitiator to the solution, sonicate until uniformly dispersed, and obtain the active monomer solution. S4: Mix an appropriate amount of active monomer solution with heteropolyacid solution, sonicate until the complex is evenly dispersed, then slowly add the film-forming resin solution dropwise to the mixed solution, shake slowly first, and then let stand until the solution layering phenomenon disappears to obtain a laser direct-write photoresist containing heteropolyacid; wherein, based on the total mass of film-forming resin, active monomer, heteropolyacid and photoinitiator as 100%, the mass percentage content of film-forming resin, active monomer, heteropolyacid and photoinitiator is 5-30 wt%, 10-60 wt%, 10-40 wt%, and 0.25-5 wt%, respectively. The film-forming resin contains at least one of ester, carbonyl, and hydroxyl groups; the active monomer is a centrally branched acrylate monomer containing hydroxyl groups; and the heteropolyacid is selected from at least one compound conforming to the following general formula: H m XY 12 O 40 nH2O Where m = 3, 4 or 5, X is the central coordinating atom, Y is the polyacid atom, and n is the number of bound water molecules, where X is P, As, Si, Ge, Sn, Ti, Zr, B, Ce, Th or U, and Y is Mo, W or V.
2. The preparation method according to claim 1, characterized in that: The organic solvents A, B, and C are each independently selected from one of ethyl acetate, ethyl formate, dimethyl sulfoxide, and propylene glycol methyl ether acetate.
3. The preparation method according to claim 2, characterized in that: Organic solvent A, organic solvent B, and organic solvent C are the same solvent.
4. The preparation method according to claim 1, characterized in that: The film-forming resin is selected from at least one of polymethyl methacrylate, polyhydroxyethyl methacrylate, polyvinyl acetate, and polyvinyl alcohol.
5. The preparation method according to claim 4, characterized in that: The molecular weight of the film-forming resin is no higher than 20,000.
6. The preparation method according to claim 5, characterized in that: The molecular weight of the film-forming resin is 3000-16000.
7. The preparation method according to claim 1, characterized in that: The active monomer is selected from at least one of pentaerythritol triacrylate, pentaerythritol dimethacrylate, and pentaerythritol diacrylate.
8. The preparation method according to claim 1, characterized in that: The photoinitiator is selected from at least one of 7-diethylamino-3-thiophenecarboxycoumarin, photoinitiator 369, photoinitiator 651, and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide.
9. The preparation method according to claim 1, characterized in that: In step S1, the concentration of the heteropolyacid solution is 5%-50wt%. In step S2, the concentration of the film-forming resin solution is 5-30 wt%. In step S3, the concentration of the active monomer in the active monomer solution is 10-50 wt%; the concentration of the photoinitiator is 0.25%-5% wt%.
10. The preparation method according to claim 9, characterized in that: In step S1, the concentration of the heteropolyacid solution is 20-40 wt%.
11. The preparation method according to claim 9, characterized in that: In step S2, the concentration of the film-forming resin solution is 9-25 wt%.
12. The preparation method according to claim 9, characterized in that: In step S3, the concentration of active monomer in the active monomer solution is 30-45 wt%.
13. The preparation method according to claim 9, characterized in that: In step S3, the concentration of the photoinitiator is 0.4%-2%.
14. A patterning method based on the laser direct-write photoresist containing heteropolyacids as described in claim 1, characterized in that: The patterning method includes the following steps: R1: Spin coating: Make the laser direct-write photoresist containing heteropolyacids transparent and uniform; place the substrate on the spin coater, drop an appropriate amount of photoresist onto the substrate, and use the spin speed to spin coat the photoresist into a uniform film. R2: Pre-baking: Place the spin-coated substrate on a baking device and heat it to completely remove the solvent; R3: Laser direct writing device setup: Arrange the femtosecond laser, optical switch, alignment device, galvanometer, objective lens, and piezoelectric platform sequentially along the optical path to form a laser direct writing device. Place the pre-baked substrate on the displacement stage of the laser direct writing device, and fill the gap between the substrate and the lens with refractive index oil. R4: Turn on the laser direct writing device, focus the objective lens on the interface between the substrate and the photoresist; load the pre-designed structure, set the laser power and scanning speed, and start the direct writing experiment; R5: Develop the direct-written substrate to obtain the photoresist pattern.
15. The patterning method as described in claim 14, characterized in that: In step R1, the carrier is pre-cleaned and selected from one of glass, quartz, silicon, and silicon nitride. The spin coating speed is 500-3000 rpm and the spin coating time is 30-60s. In step R2, the pre-baking temperature is 90-95℃ and the heating time is 1-5 min.
16. The patterning method as described in claim 14, characterized in that: In step R4, the femtosecond laser wavelength is between 400-900 nm, the laser power is 1-50 mW, and the scanning speed is 1000-10000 μm / s.
17. The patterning method as described in claim 14, characterized in that: In step R5, the development is carried out as follows: first, develop in a primary developer for 5-30 seconds, and then develop in a secondary developer for 5-30 seconds; the primary developer is selected from one or any mixture of several of acetone, ethanol, isopropanol, propylene glycol methyl ether acetate, toluene, xylene, and dichloromethane; the secondary developer is selected from isopropanol or ethanol.
Citation Information
Patent Citations
Coloring-material dispersion, composition, film, optical filter, and display device
CN112088192A
High-refractive-index laser direct writing photoresist and preparation method of high-curvature photon lead
CN115755525A